Green Diesel: Biomass Feedstocks, Production Technologies, Catalytic Research, Fuel Properties and Performance in Compression Ignition Internal Combustion Engines - Savvas L. Douvartzides; Nikolaos D. Charisiou; Kyriakos N. Papageridis; Maria A. Goula (Energies, 2019)
The present investigation provides an overview of the current technology related to the green diesel, from the classification and chemistry of the available biomass feedstocks to the possible production technologies and up to the final fuel properties and their effect in modern compression ignition internal combustion engines. Various biomass feedstocks are reviewed paying attention to their specific impact on the production of green diesel. Then, the most prominent production technologies are presented such as the hydro-processing of triglycerides, the upgrading of sugars and starches into C15–C18 saturated hydrocarbons, the upgrading of bio-oil derived by the pyrolysis of lignocellulosic materials and the “Biomass-to-Liquid” (BTL) technology which combines the production of syngas (H2 and CO) from the gasification of biomass with the production of synthetic green diesel through the Fischer-Tropsch process. For each of these technologies the involved chemistry is discussed and the necessary operation conditions for the maximum production yield and the best possible fuel properties are reviewed. Also, the relevant research for appropriate catalysts and catalyst supports is briefly presented. The fuel properties of green diesel are then discussed in comparison to the European and US Standards, to petroleum diesel and Fatty Acid Methyl Esters (FAME) and, finally their effect on the compression ignition engines are analyzed. The analysis concludes that green diesel is an excellent fuel for combustion engines with remarkable properties and significantly lower emissions.